Innovation in sustainable infrastructure: advanced analysis of the mechanical properties of permeable pavers for resilient and eco-efficient construction - Alvansazyazdi, Mohammadfarid (2025)
The present research focused on the design and development of a permeable paver that allows rainwater to filter into the subsoil, thereby reducing the amount of water entering sewer systems and minimizing the impact of urban flooding. The process began with the evaluation of compressive strength and permeability in test cylinders, selecting the most suitable mixtures for subsequent paver fabrication. Once the optimal designs were chosen, key properties such as indirect tensile strength, water absorption, and permeability were assessed. The results showed that by using a high-range water-reducing admixture, indirect tensile strengths of 3.4, 3.9, and 4.5 MPa were achieved, with permeabilities of 2.30, 1.93, and 1.15 mm/s, respectively. These findings demonstrate that the developed pavers successfully meet the mechanical strength requirements necessary for use in interlocking pavements.